Tax failure: New Zealand's short-lived First World War Excess Profits Tax. (2nd January 2019) - Vosslamber, Rob
ABSTRACT: In 1915, Great Britain introduced an Excess Profits Duty to help fund the costs of World War One and to ensure social cohesion in the context of war. New Zealand followed the Imperial lead in 1916. Unlike in other British Dominions, the New Zealand Excess Profits Tax was discontinued after only one year. This article discusses the New Zealand Excess Profits Tax. It reviews the context of this tax within the British Empire, the development of the tax in New Zealand, and considers reasons for its early demise. This narrative provides a basis for future research into the practice of taxation in wartime, and the relationship between tax and society.